TRADISI BAPONGKA MASYARAKAT SUKU BAJO - Muhammad, Ropandi J (Historia Islamica: Journal of Islamic History and Civilization, 2024)
This research was carried out because there is still a lack of researchers who conduct research one the traditions in Kalumbatan Vilagge, especially the Bapongka tradition. In addition, it is also to find out the history and process of implementation and development of the Bapongka tradition in the muslim community of the Bajo tribe of Kalumbatan Vilagge. This type of research uses the historical method. According to Glibert J. Garraghan, the historical research method is a set of systematic rules and principles to colletc historical sources efeectively, critically evaluate them, and propose a synthesis of the results achieved in written form. The Bapongka tradition of Kalumbatan Vilagge is brought by the Bajo tribe who are in Kalumbatan Vilagge, the entry of the Bajo tribe is along with the Bapongka tradition because the Bapongka tradition is part of the Bajo tribe culture where the Bapongka tradition of the Bajo tribe’s ancestors who are stil carried out today and have developed and kept up with the times. The history of the Bapongka tradition exists along with the existence of the Bajo tribe which is spread to various regions, who make every trip while at sea. In the implemantation of Bapongka people use soppe or leppa boats and carry out the Bapongka tradition for weeks or even months. The development of the Bapongka tradition can be seen form the change in fishing gear, boats and places used as resting places by the Bajo tribe people which were initially traditional to become more modern